IDENTIFIKASI FAKTOR RESIKO TERJADINYA INFEKSI KECACINGAN PADA MURID SEKOLAH DASAR NEGERI 1 BAGIK POLAK BARAT DI KECAMATAN LABUAPI KABUPATEN LOMBOK BARAT - Lale Maulin Prihatina (Unram Medical Journal, 2021)
Background: Helminthiasis is infestation with one or more intestinal parasitic worms occurred in human body, mostly caused by roundworms (Ascaris lumbricoides), whipworms (Trichuris trichiura), and hookworms (Necator americanus and Ancylostoma duodenale). More than 1.3 billion people are infected with soil-transmitted helminth infections worldwide. Soil-Transmitted Helminthiasis (STH) can be contracted by humans in various age groups, however children are the most affected by the consequences of the infections. Over 400 million school-age children are infected by STH, and their cognitive and educational performances are affected by these infestations. Purpose: The objective of this study is to analyze varied risk factors of STH in Primary School Students of Sekolah Dasar Negeri 1 Bagik Polak, Labuapi Subdistrict, West Lombok Method: An observational, cross-sectional study was conducted, using questionnaire and structured interview. Risk Factors were evaluated through students' defecation behavior, practices on hand hygiene, footwear use, and other sanitation-related practices and knowledge. Fecal examinations were performed to establish helminthiasis diagnosis. A Chisquare test was used to analyze the collected data. Results and Conclusions: STH were diagnosed in 8.6% of respondents. There was no correlation identified between mother's' level of knowledge and diagnosis of STH (87.7% with good level of knowledge in regard to STH). Significant correlations were identified between diagnosis of STH and students' level of personal hygiene (p=0.044), and family members' practices in regard to helminthiasis prevention (p=0.01).